2017
DOI: 10.1111/1440-1681.12719
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B cell is critical in bone union process through suppressing proinflammatory cytokines and stimulating Foxp3 in Treg cells

Abstract: Bone fractures may result in delayed union (DU) or non-union (NU) in some patients. Evidence suggests that the skewing of the immune system toward the proinflammatory type is a contributing factor. Because B cells were previously found to infiltrate the fracture healing site at abundant levels, we examined the regulatory B cells (Bregs) in DU/NU patients. In bone fracture patients with normal healing, the frequency of interleukin (IL)-10-expressing B cells was significantly upregulated in the early healing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 30 publications
1
50
0
1
Order By: Relevance
“…Sun et al. reported that regulatory B cells were critical in the bone union process by stimulating regulatory T cells . Song et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al. reported that regulatory B cells were critical in the bone union process by stimulating regulatory T cells . Song et al.…”
Section: Discussionmentioning
confidence: 99%
“…Also, IL6 knockout mice have delayed callus mineralization and maturation (Wallace, Cooney, Englund, & Lubahn, ; Yang et al., ), but mice that lack the IL1 receptor do not show considerable changes (Lange et al., ). Even though IL10 or other anti‐inflammatory cytokines are abundantly present in the fracture haematoma, their role during fracture healing remains unclear (Hauser et al., ; Sun et al., ).…”
Section: Preamblementioning
confidence: 99%
“…This mechanism seems to depend on regulatory B and T lymphocytes (B regs and T regs ), as they were shown to participate in fracture healing. B regs were presented to suppress the inflammatory phase secreting antiinflammatory cytokines IL-10 (interleukin-10) and TGF-β (transforming growth factor-β), and enhancing maturation of T regs [15]. At the early phase of the reparative processes, they probably prevent from auto aggression against infiltrating progenitors, thus enabling them to proliferate and differentiate into bone forming cells.…”
Section: Inflowing Inflammatory Cellsmentioning
confidence: 99%